Effect of Hydrated Carbon 60 Fullerene on Frozen Ram Semen Quality - Gungor, Ibrahim Halil; Cinkara, Serap Dayan; Acisu, Tutku Can; Arkali, Gozde; Koca, Recep Hakki; Akarsu, Serkan Ali; Turk, Gaffari (Mary Ann Liebert, Inc, 2022)
The aim of this study was to evaluate the effect of hydrated carbon 60 fullerene (C(60)HyFn) on ram semen quality during cryopreservation. Three ejaculates from each of seven Akkaraman rams were collected using an artificial vagina during the nonbreeding season and pooled. Pooled semen samples were divided into 10 equal parts and diluted with tris + egg yolk extender not containing (control) and containing 100, 200, 400, and 800 nM and 1, 5, 10, 20, and 40 mu M C(60)HyFn at 37 degrees C. After addition of 5% glycerol and an equilibration process for 3 hours, the samples were frozen in 0.25-mL straws in an automatic freezing device at -140 degrees C and stored in a liquid nitrogen container. Straws were thawed 24 hours after freezing and analyzed immediately with no incubation period. Motility, kinematic parameters, abnormality, vitality, hypo-osmotic swelling test (HOST), and oxidative stress levels were analyzed in thawed semen. Compared with the control, 200, 400, and 800 nM and 1 and 5 mu M C(60)HyFn doses increased motility and HOST values and decreased the dead sperm rate. When compared with the control, addition of C(60)HyFn significantly decreased malondialdehyde levels (between 200 nM and 40 mu M doses) and significantly increased glutathione peroxidase (between 800 nM and 40 mu M doses) and catalase (between 1 and 40 mu M doses) activities. In conclusion, results of this study show that the C(60)HyFn nanoparticles are nontoxic to ram semen and their supplementation in the extender is beneficial to sperm motility and membrane integrity after freeze-thawing.
Keywords: freeze-thawing; hydrated carbon 60 fullerene; oxidative stress; ram; semen